Prevalence of prediabetes and risk of CVD mortality in individuals with prediabetes alone or plus hypertension in Northeast China: insight from a population based cohort study - Ling Yue; Yuanmeng Tian; Mingxi Ma; Li Jing; Qun Sun; Lei Shi; Jixu Sun; Weizhong Wang; Guangxiao Li; Liying Xing; Shuang Liu (BMC, 2024)
Abstract Background To evaluate the current prevalence of prediabetes in northeast China, and further determine the association between prediabetes alone or coexistent with hypertension and cardiovascular disease (CVD) mortality. Methods In the prospective study, 15,557 participants without diabetes among aged ≥40 years in northeast China, were followed for a median of 5.5 years. Following the American Diabetes Association, prediabetes was defined as fasting plasma glucose (FPG) range of 5.6-6.9 mmol/L or glycated hemoglobin (HbA1c) range of 5.7-6.4% in people without diabetes. Results The prevalence of prediabetes was 44.3% among population aged ≥40 years in northeast China. Prediabetes alone did not promote risk of CVD mortality. However, when the subgroups were stratified by hypertension, the CVD mortality risk in prediabetes plus hypertension subjects increased significantly compared with population without prediabetes and hypertension. Multivariate-adjusted hazard ratios for CVD mortality in prediabetes subgroups plus hypertension were 2.28 (95% CI: 1.50, 3.47) for those diagnosed by FPG < 5.6 mmol/L & HbA1c 5.7-6.4%, 2.18 (95% CI: 1.53, 3.10) for those diagnosed by FPG 5.6-6.0 mmol/L & HbA1c < 6.5% and 2.35 (95% CI: 1.65, 3.35) for those diagnosed by FPG 6.1-6.9 & HbA1c < 6.5% compared with the reference group. Moreover, the percentage of hypertension in prediabetes subjects was high (60.4%), but the awareness, treatment and control rates were far from satisfactory (45.3, 35.1 and 4.8%, respectively). Conclusions The prevalence of prediabetes remains high in northeast China, and the CVD mortality was elevated significantly in prediabetes coexistent with hypertension. Considering the high percentage and low control rate of hypertension in prediabetes, strategies focused on HbA1c screening, FPG lowering and blood pressure management should be emphasized in northeast China.